2018
DOI: 10.1016/j.maturitas.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypovitaminosis D with triceps brachii muscle fatigability among older women: Findings from the EPIDOS cohort

Abstract: A B S T R A C TBackground: Vitamin D affects physical performance in older adults. Its effects on muscles, notably on muscle strength, remain unclear. The objective of this cross-sectional study was to determine whether hypovitaminosis D is associated with triceps brachii muscle fatigability in community-dwelling older women. Methods: A randomized subset of 744 women aged ≥75years from the EPIDOS cohort was categorized into two groups according to triceps brachii muscle fatigability, defined as loss of strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Further, the soleus muscle demonstrated higher initial fatigability with repetitive stimulation, and slower recovery after the yearly injection; fatigue in a postural muscle could contribute to an increased risk of falls by limiting toe clearance when lifting the foot, for example. Interestingly, this is similar to associations between low vitamin D and increased fatigability [20]. Collectively, the data support the idea that muscular changes in response to a very large bolus of vitamin D could be harmful and contribute to the risk of falls observed in human participants.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, the soleus muscle demonstrated higher initial fatigability with repetitive stimulation, and slower recovery after the yearly injection; fatigue in a postural muscle could contribute to an increased risk of falls by limiting toe clearance when lifting the foot, for example. Interestingly, this is similar to associations between low vitamin D and increased fatigability [20]. Collectively, the data support the idea that muscular changes in response to a very large bolus of vitamin D could be harmful and contribute to the risk of falls observed in human participants.…”
Section: Discussionsupporting
confidence: 82%
“…Vitamin D deficiency has been associated with muscle weakness and fatigue [20]. As such, vitamin D supplementation is a common treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of classical OH was higher than in most previous studies. In 7 studies of individuals with a mean age of 72-81 years, the prevalence of classical OH was 7% (primary care patients), 18%, 21.5%, and 27% (general population cohorts), 35% (geriatric patients), as well as 38.5% and 50% (hospitalized patients) [12][13][14][15][16][17][18]. However, the first 3 studies measured BP only at 3 minutes, and the fourth study used only systolic BP, which could decrease sensitivity [16][17][18].…”
Section: Prevalencementioning
confidence: 99%
“…In 7 studies of individuals with a mean age of 72-81 years, the prevalence of classical OH was 7% (primary care patients), 18%, 21.5%, and 27% (general population cohorts), 35% (geriatric patients), as well as 38.5% and 50% (hospitalized patients) [12][13][14][15][16][17][18]. However, the first 3 studies measured BP only at 3 minutes, and the fourth study used only systolic BP, which could decrease sensitivity [16][17][18]. A Dutch study of patients with falls and syncope and a mean age of 80 years, which measured standing BP after 1, 3, 5, 7, 9, and 10 minutes, found that 32% had continuous classical, 16% had transient classical, and 8% had delayed OH [19].…”
Section: Prevalencementioning
confidence: 99%
“…This bone loss can lead to mineralization defect, osteoporosis and osteomalacia in the case of prolonged exposure. Vitamin D deficiency also exposes one to a risk of fractures due to bone fragility and an increased risk of muscle fatigability [ 30 ] and falls [ 31 ].…”
Section: Vitamin D and Bone Healthmentioning
confidence: 99%